(untitled) (American Journal of Business Management, Economics and Banking, 2025)
In this article, the importance of internal audit in the corporate governance system, tariffs given to corporate governance, their variety, corporate governance models, Anglo-Saxon model, Continental-European model, Mixed model, regulatory documents on corporate governance, participants and the importance and necessity of internal audit among these participants are discussed.